2007
DOI: 10.1111/j.1471-4159.2007.04457.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoleukodystrophy: subcellular localization and degradation of adrenoleukodystrophy protein (ALDP/ABCD1) with naturally occurring missense mutations

Abstract: Mutation in the X-chromosomal adrenoleukodystrophy gene (ALD; ABCD1) leads to X-linked adrenoleukodystrophy (X-ALD), a severe neurodegenerative disorder. The encoded adrenoleukodystrophy protein (ALDP/ABCD1) is a half-size peroxisomal ATP-binding cassette protein of 745 amino acids in humans. In this study, we chose nine arbitrary mutant human ALDP forms (R104C, G116R, Y174C, S342P, Q544R, S606P, S606L, R617H, and H667D) with naturally occurring missense mutations and examined the intracellular behavior. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Although we and others have shown that missense X-ALD mutations result in ALDP instability in mammalian cells [56,58] (Figure 4), in a previous study, we noticed that cts mutants which have 'protein-absent', disease-associated equivalents in human ABCD1 were expressed as stable correctly targeted proteins in Arabidopsis [46]. We therefore tested whether ALDP variants bearing missense mutations which result in protein mistargeting or instability in mammalian cells would behave similarly when expressed in plant cells.…”
Section: X-ald Mutant Proteins Are Expressed At the Peroxisome In Plamentioning
confidence: 92%
See 1 more Smart Citation
“…Although we and others have shown that missense X-ALD mutations result in ALDP instability in mammalian cells [56,58] (Figure 4), in a previous study, we noticed that cts mutants which have 'protein-absent', disease-associated equivalents in human ABCD1 were expressed as stable correctly targeted proteins in Arabidopsis [46]. We therefore tested whether ALDP variants bearing missense mutations which result in protein mistargeting or instability in mammalian cells would behave similarly when expressed in plant cells.…”
Section: X-ald Mutant Proteins Are Expressed At the Peroxisome In Plamentioning
confidence: 92%
“…We therefore tested whether ALDP variants bearing missense mutations which result in protein mistargeting or instability in mammalian cells would behave similarly when expressed in plant cells. In addition to the temperature-sensitive mutants identified above, a range of X-ALD mutants with different intracellular fates was selected [58] ( Table 2), with the goal of comparing the capacity of plant and mammalian cells for sensing and turnover of defective peroxisomal membrane proteins. These included relatively common mutants which are unstable in fibroblasts, but which can be rescued by the application of proteasome inhibitors (p.Ser606Leu, p.Arg617His and p.His667Asp), the p.Arg104Cys mutant in which degradation of ALDP cannot be prevented by proteasome inhibitors and the p.Tyr174Cys mutant which is Table 2 …”
Section: X-ald Mutant Proteins Are Expressed At the Peroxisome In Plamentioning
confidence: 99%
“…Indeed misfolded peroxisomal ABC transporters are subject to quality control, as revealed by missense mutations associated with X-ALD, the majority of which result in markedly reduced protein levels at the peroxisome membrane ). The precise quality control mechanisms remain to be investigated but the existence of several checkpoints has been suggested (Takahashi et al 2007). Interestingly, X-ALD mutants which were subject to proteasomal degradation in human fibroblasts were correctly targeted and stable when expressed in plant cells, an effect which was not wholly explicable by low temperature rescue of protein folding .…”
Section: Targetingmentioning
confidence: 99%
“…22) ABCD1 cDNA was cloned into pcDNA4HisMax vector by TA-cloning. The human ABCD1 gene in pcDNA3.1+ / ABCD1 (kindly provided by Dr. K. Kamijo, Tohoku University) was used as the template.…”
Section: Methodsmentioning
confidence: 99%
“…24) Immunofluorescence analysis was performed as described previously. 22) Human glioblastoma U87 cells were seeded on dishes containing coverslips in EMEM with 10% FBS. The cells on the coverslips were washed three times in PBS and fixed with 3% formaldehyde in PBS for 20 min.…”
Section: Methodsmentioning
confidence: 99%